Response evaluation of direct displacement based and force based design method for RC frames - Sheth, Rutvik K.; Soni, Devesh P. (Journal of Structural Engineering, 2024)
Seismic design of buildings has traditionally been force-based. It is widely understood now that it is not the force but displacement, which can be directly related to damage. The alternative design approaches are gradually becoming popular in recent times. Design Methodology for Direct Displacement Based Design Method (DDBD) has been presented here in the context of IS code as an alternative to conventional Forced Based Design (FBD). The paper attempts to design moment resisting RC frame using Displacement Based Design method. Regular RC frames of 4, 6, 8, 10, 12 and 15 stories were designed using FBD and DDBD procedure for the parametric study. Evaluation of Response Modification Factor is done using static nonlinear pushover analysis. Also Nonlinear Time History Analysis (NLTHA) was performed for a set of seven ground motions from past Indian Earthquake. Pushover Analysis and NLTHA were carried out using DRAIN-2DX program for Performance evaluation of these RC frames.It is observed that design base shear of the frames designed by DDBD is less compared to those designed by FBD. Further, the DDBD designed frames yield higher Response Modification Factor as compared to FBD, implying higher capacity of structure to dissipate energy through inelastic behavior.